Mind the First Step: The Intrapersonal Effects of Affect on the Decision to Initiate Negotiations under Bargaining Power Asymmetry - Kapoutsis, Ilias; Volkema, Roger; Lampaki, Antonia (Frontiers in Psychology, 2017)
We undertook two vignette studies to examine the role of affect (trait and state) and bargaining power on initiating negotiations, an often overlooked stage of the negotiation process. Using a job negotiation opportunity, we examine three distinct phases of the initiation process – engaging a counterpart, making a request, and optimizing a request. Study 1 examines the effects of two affect dispositions (happiness and sadness), under power asymmetry (low vs. high bargaining power), on the three initiation behaviors. We found that power is pivotal to the decision to engage, request and optimize. Also, sadness reduces the likelihood of initiation when power is high but is immaterial when power is low. In contrast, individuals who tend to be happy can reverse the adverse effect of powerlessness on requesting, but not on engaging and optimizing. However, happiness does not carry over a positive effect on negotiation initiation, over and above that of power. Study 2 investigated the role of trait affect when individuals are in power asymmetry and when they are induced with sadness or happiness. We found that those with a happy disposition initiate more (engage, request, and optimize) when power is high and experience incidental sadness. Overall, these findings qualify previous research on negotiation initiation and highlight the importance of trait affect and its interaction with state affect as additional driving forces and of power as a boundary condition.